PENGARUH TESTIMONI DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS GLOW DI KABUPATEN BADUNG - Ni Nyoman Alit Sriantini; Ni Made Hartini (Journal Research of Management, 2022)
This study aims to determine the problems raised in this study are whether testimonials affect the purchasing decisions of Ms Glow products in Badung Regency, whether word of mouth affects the purchasing decisions of Ms Glow products in Badung Regency and which variables have a dominant influence on purchasing decisions for Ms Glow products. Glow in Badung Regency. The population in this study amounted to 112 people with purposive sampling technique, namely Ms Glow consumers who are at least 17 years old. The data collection technique used is a questionnaire distributed using google form to the respondents. The data analysis technique used was descriptive analysis, quantitative analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis, t test. The results of the analysis show the Y regression model, which means that testimonials have a positive and significant effect on Ms Glow's Product Purchase Decisions in Badung Regency, with a value of 0.000. This means that if the testimonials are getting better, the Purchase Decision will increase. word of mouth has a positive and significant effect on purchasing decisions at Ms Glow in Badung Regency with a value of 0.030. This means that if the word of mouth is getting better, then the Purchase Decision will increase. Testimonials have a dominant influence on purchasing decisions for Ms Glow's products in Badung Regency. Ms Glow in Badung Regency is expected to pay close attention to company testimonials such as attention given to consumers, consumer buying interest, consumer needs or desires, as well as consumer confidence and actions in buying Ms Glow products.